Guidelines for Counsellor Education in Canada - Peavy, Vance; Robertson, Sharon; Westwood, Marvin (Canadian Journal of Counselling and Psychotherapy, 2012)
In June, 1981, the Canadian Guidance and Counselling Association (CGCA) accepted in principle a set of guidelines for counsellor education programs in Canada. In this article, the authors review the historical development of these guidelines, identify some definitions and working principles upon which they are based, and present them in their current form. The importance of, and advantages in having, a set of guidelines are discussed. Finally, unaddressed issues are considered.